Evaluation of the Implementation of the Green Banking Concept at Bank XYZ - Tegar Wibowo Wahyuditomo (Eduvest - Journal of Universal Studies, 2024)
Indonesia is committed to Undang-Undang Nomor 16 Tahun 2016 concerning the Paris Agreement on Climate Change. To support this commitment, the role of banking, including Bank XYZ, is crucial in financing clean energy projects and other business sectors. Although Bank XYZ has shown growth in green financing since 2016, there are notes regarding financing in the coal sector between October 2018 and October 2020, as well as a decline in the ranking in the 2022 Bank Ranking Report. Therefore, an evaluation of the concept of green banking at Bank XYZ is needed to maintain its growth and ensure the effectiveness of its implementation from 2017 to 2022. This research employs a qualitative approach to analyze the implementation of green banking at Bank XYZ. The evaluation is conducted through interviews with the Risk Management Division and an analysis of sustainability reports using the Green Banking Disclosure Index (GBDI). Bank XYZ has proven to implement the concept of green banking transparently, but there are shortcomings such as a lack of transparency in sustainability budgeting, attention to debtors, internal controls, sustainability campaigns, and the use of renewable technology. This research is expected to enhance the quality of green banking implementation at Bank XYZ, support environmental preservation, and address existing weaknesses.